European R&D networks: a snapshot from the 7th EU Framework Programme. Issue 5 (18th August 2018) - Amoroso, Sara; Coad, Alex; Grassano, Nicola
ABSTRACT: Recent empirical studies have investigated the territorial impact of Europe's research policies, in particular the contribution of the European Framework Programmes to the integration of a European Research Area. This paper deepens the analysis on the integration and participation of peripheral regions, by focusing on the differences in intensity and determinants of inter-regional collaborations across three groups of collaborations. We consider collaborations among more developed regions, between more and less developed regions, and among less developed regions. Building on the recent spatial interaction literature, this paper investigates the effects of physical, institutional, social and technological proximity on the intensity of inter-regional research collaboration across heterogenous European regions. We find that the impact of disparities in human capital and technological proximity on regional R&D cooperation is relevant and differs across subgroups of collaborations. Moreover, despite the efforts of integrating marginal actors, peripheral regions have lower rates of collaborations.